2021
DOI: 10.1038/s41598-021-00849-8
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the Frenkel–Kontorova and Ising models for investigation the magnetic properties of a ferromagnetic monolayer on a stretching substrate

Abstract: In the article, computer simulation on the behavior of a ferromagnetic thin film on a non-magnetic substrate by computer simulation is performed. The substrate is described by the two-dimensional Frenkel–Kontorova potential. The Ising model is used to describe the magnetic properties of a two-dimensional ferromagnetic film. The Wolf cluster algorithm is used to model the magnetic behavior of the film. A square lattice is considered for an unperturbed ferromagnetic film. Computer simulations show that mismatch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The dependence of the exchange integral for the spin–spin interaction on distance has a main influence on the change in magnetic properties. Studies of the substrate deformations effect on the magnetic properties of single-layer 2D films on a non-magnetic substrate [ 11 , 12 , 13 ] have shown that uniform substrate deformations can lead to non-uniform film deformations at the free ends of the film. Islands with increased concentration of atoms are formed in the film when the substrate is compressed.…”
Section: Introductionmentioning
confidence: 99%
“…The dependence of the exchange integral for the spin–spin interaction on distance has a main influence on the change in magnetic properties. Studies of the substrate deformations effect on the magnetic properties of single-layer 2D films on a non-magnetic substrate [ 11 , 12 , 13 ] have shown that uniform substrate deformations can lead to non-uniform film deformations at the free ends of the film. Islands with increased concentration of atoms are formed in the film when the substrate is compressed.…”
Section: Introductionmentioning
confidence: 99%
“…We propose a 1D quantum microscopic model with interacting particles subjected to an onsite potential and time-dependent perturbations. Our model intends to be a general drastic idealization of systems like real materials, trapped ions in optical lattices or low dimensional lattice structures constructed on a substrate [18][19][20][21]. The study is carried out numerically based on the Keldysh non-equilibrium Green function formalism [22].…”
Section: Introductionmentioning
confidence: 99%